COMPARISON OF THE PERCENTAGE OF BODY FAT BETWEEN BIOELECTRICAL IMPENDANCE METHODS – TETRAPOLAR VS BIPOLAR (Fiep Bulletin - online, 2011)
The accurate estimative of body composition gives important information in physical exercise programs, weight control, maintenance of physiological function, therefore are related to individuals health and quality of life. The objective of this study was to verify whether there are any differences between the results of the evaluation of methods of body composition by tetra polar and bipolar bioelectrical impedance analysis (BIA). The sample consisted of 18 healthy male volunteers between the ages of 21,74,4. These volunteers regularly exercise and show normalcy in their BMI. Tests were carried out on body composition of tetra polar BIA (MALTRON BF-906) and bipolar lower limb (PLENNA TIN-99). Results were collected while the subjects were fasting for 4 hours, abstinent from alcohol and physical activity for 24 hours, rested and urinated 10 minutes prior to the tests. The results indicated significant differences between the BIA methods (p
Keywords: body composition; fitness; bioelectrical impedance